Environmental drivers of litter- and soil-dwelling springtail communities across European forests, assessed by morphotaxonomy and soil DNA metabarcoding - Ivano Brunner; Beat Frey; Maria J.I. Briones; Jérome Cortet; Xavier Domene; Juliane Filser; Aline Frossard; Davey L. Jones; Paul Henning Krogh; Juha Mikola; Olaf Schmidt; José Paulo Sousa; et al. (Applied Soil Ecology, 2026)

Increased heat and drought scenarios modify the toxicity of a fungicide mainly in low concentrations on Folsomia candida (Collembola) life-history - Borbála Szabó; Juliane Filser (Journal of Soils and Sediments, 2026)
Purpose IPCC predicted at least 1.5 °C increase of global temperature in the next 20 years, but this increase will be higher on land. At the same time, the frequency of extreme weather events will increase. Pesticide pressure is still an actual problem worldwide, but different climate scenarios are not part of the standard test procedures during chemical registration. Methods We investigated whether increased temperature with or without drought changes the toxicity of a succinyl dehydrogenase inhibitor (SDHI) fungicide, Fontelis 20 SC (penthiopyrad) on Folsomia candida (Collembola). We quantified the juvenile number, the relative growth, the egg number, the egg volume and the growth-reproduction trade-off, and repeated the measurements after a recovery period. Results The individual life-history parameters reacted very differently to the climate scenarios. In general, the highest concentration imposed a limit to juvenile number, relative growth, total egg number, and total reproduction investment. Therefore, all groups end up at a very similar value at the highest concentration while at more realistic lower concentrations the different climate scenarios exhibited pronounced differences. Drought decreased the performance of the Collembola but also mitigated the effects of the fungicide whereas temperature increase intensified the fungicide effect, but also facilitated the recovery. Conclusion We found pronounced effects of the climatic scenarios, especially in the high temperature treatment, where full recovery was not possible.

Non-linear effects of Fontelis 20 SC (fungicide) on gut microbiota relate to changes in reproduction of Folsomia candida (Collembola) - Borbála Szabó; Elisabeth K. Riedel; Marko Rohlfs; Juliane Filser (Applied Soil Ecology, 2026)